Self-prediction and patient health: Influencing health-related behaviors through self-prophecy - Sprott,David E.; Spangenberg,Eric R.; Knuff,David; Devezer,Berna (Medical Science Monitor, 2006)
People asked to make a self-prediction about a socially normative behavior are significantly more likely (than a comparable control group) to perform the behavior in a manner consistent with social norms. Making a behavioral self-prediction has been demonstrated to increase attendance to a health club, consumption of healthy snacks, and commitment to a health and fitness assessment. Empirical evidence indicates that thisself-prophecy effect is due to dissonance-based motivation generated by the prediction request. In this article, we present self-prediction as a practical and effective tool that health care professionals can use to favorably influence a variety of health-related, patient behaviors. Previous studies on health behaviors are aggregated using meta-analytical techniques to determine the magnitude of self-prediction effects on health-related behaviors. To account for potential errors of exclusion in our analysis, a file drawer analysis is also conducted. Our analysis suggests that self-prophecy manifests as a small- to medium- effect size when used in the context of modifying health-related behaviors. Providing support for the robustness of this effect, our file drawer analysis indicated that 270 further studies with null results would be needed to negate our conclusions regarding the effect. Based on previous research and findings of the current meta-analysis, we are confident that health care professionals can effectively employ self-prediction as a method for promoting healthier behaviors and lifestyles among their patients. Implications for medical practice and allied health fields, as well as areas of future research, are identified.
Keywords: Marketing; OSU-Cascades